ChemInform Abstract: Synthesis of α‐Amidoketones from Vinyl Esters via a Catalytic/Thermal Cascade Reaction. Issue 41 (September 2016) - Holthusen, Katharina; Leitner, Walter; Francio, Giancarlo
Abstract: This cascade reaction includes hydroformylation, condensation with a primary amine, and a rearrangement step giving water as the only byproduct.